"Dolgota dnej" di V. Rafeenko. Esplorazioni identitarie di un autore (russofono) ucraino - Maria Gaia Ruggiero (eSamizdat)
This article explores the life and prose of Ukrainian author Vladimir Rafeenko (ukr. Volodymyr Rafeyenko, Donetsk, 1969), with a focus on his latest russophone novel, Dolgota dnei [The Length of Days, 2017]. Rafeenko’s personal and professional trajectory is examined in its complex dialogue with the Russian and Ukrainian sociopolitical contexts, in order to highlight the close interrelation between extra-literary factors, identity reflection and linguistic practices in the author’s literary experience. Specifically, Dolgota dnei is interpreted as a manifesto of the national consciousness developed by the author following the outbreak of the conflict in Donbas. In the novel, Rafeenko deconstructs the linguistic determinism promoted by political discourse, proposing an alternative perspective on Russian language and culture and a new, civic and multilingual conception of ‘Ukrainianness’.